Validitas Perceraian Melalui Media Sosial: Analisis Ontologi, Epistemologi, dan Aksiologi terhadap Hukum Perkawinan Islam - Rifki Asfarina Fillah; Ramsiah Tasruddin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The rapid development of digital technology has brought about a contemporary phenomenon where husbands pronounce divorce (talak) to their wives through social media, which raises profound philosophical and juridical challenges. This study aims to analyze the legal validity of social media-based divorce (ontology), its methods of legal proof and verification (epistemology), as well as its sociological impacts and the protection of post-divorce rights for wives and children (axiology). Employing a qualitative method with a library research approach, this study examines the issue from both Islamic law and Indonesian positive law perspectives. The results demonstrate that ontologically, the majority of Islamic scholars (jumhur ulama) consider social media divorce via text messages valid, as it is analogized (diqiyaskan) with written divorce (thalaq bi al-kitabah). Epistemologically, digital evidence such as WhatsApp messages is recognized as valid legal evidence in the Religious Court under the Electronic Information and Transactions (ITE) Law, yet it requires strict verification (tabayyun) to ensure authenticity and the husband's actual intent (qashad). Axiologically, while digital divorce can be deemed valid, the divorce process must strictly be conducted before the Religious Court to ensure justice, protection, and the fulfillment of financial and social rights for both wives and children.